The Prognostic and Functional Impact of Multimorbidity in Systemic Sclerosis - Jessica L. Fairley; Dylan Hansen; Susanna Proudman; Joanne Sahhar; Gene‐Siew Ngian; Diane Apostolopoulos; Jennifer Walker; Lauren V. Host; Wendy Stevens; Mandana Nikpour; Laura Ross (ACR Open Rheumatology)
Objective Our objective was to define the frequency and impact of multimorbidity in systemic sclerosis (SSc). Method Australian Scleroderma Cohort Study participants meeting American College of Rheumatology/EULAR criteria were included. Charlson Comorbidity Index scores were calculated at each visit, with multimorbidity defined as scores ≥4. Generalized estimating equations were used to model longitudinal data in multivariable models including age, sex, subclass, interstitial lung disease, and pulmonary arterial hypertension status. Survival was analyzed using Cox hazard modeling. Results Of 2,000 participants, 85% were female, 27% had diffuse SSc, and 20% had multimorbidity. Among those with multimorbidity, key comorbidities were hypertension (81%), dyslipidemia (67%), obstructive lung disease (50%), malignancy (49%), and ischemic heart disease (IHD) (40%). Multimorbidity was associated with worse survival (hazard ratio [HR] 1.57, 95% confidence interval [CI] 1.30–1.91, P < 0.01). Renal disease had the largest impact (HR 2.41, 95% CI 1.46–3.98, P < 0.01), followed by left ventricular dysfunction (HR 1.76, 95% CI 1.21–2.57, P < 0.01), anticoagulation (HR 1.64, 95% CI 1.28–2.08, P < 0.01), and IHD (HR 1.45, 95% CI 1.16–1.80, P < 0.01). In multivariable modeling, multimorbidity was associated with poorer physical function (regression coefficient [RC] +0.17 units, 95% CI 0.13–0.21, P < 0.01). Peripheral vascular disease had the largest impact on physical function (RC +0.26 units, 95% CI 0.18–0.34, P < 0.01), followed by left ventricular dysfunction (RC +0.23 units, 95% CI 0.14–0.33, P = 0.01), IHD (RC +0.22 units, 95% CI 0.17–0.28, P < 0.01), and obstructive lung disease (RC +0.19 units, 95% CI 0.14–0.24, P < 0.01). Conclusion Multimorbidity occurred in 20% of patients in a large SSc cohort and was an important determinant of both prognosis and physical function. Effective treatment of non‐SSc morbidity may improve outcomes for patients with SSc.